Impact of COVID-19 Pandemic on Consumers Purchase Behaviour Through Social Media - Lim, Kah Boon; Yeo, Sook Fern; Tan, Cheng Ling; Wong, Wei Wen (RSF Conference Series: Business, Management and Social Sciences, 2025)
Social media refers to any digital tool that allows users to quickly create and share content with the public. The COVID-19 pandemic has indirectly changed consumers' purchasing habits, causing them to shift from traditional store purchases to online retail store purchases. Social media also changes the specialized strategies among sellers and purchasers. The main objective of this study is to investigate the factors affecting consumer purchase behaviour through social media during the COVID-19 outbreak. A set of the self-administered questionnaire has been distributed to 215 targeted young adults in three states of Malaysia which are Johor, Melaka and Selangor. The four independent variables are price, convenience, product variety and risk, are tested on their relationship towards the dependent variable, which is the purchase behaviour of consumers during the COVID-19 outbreak. The collected data were keyed into SPSS version 26 and followed by using Partial Least Square Structural Equation Modeling (PLS-SEM 3.3.3) to assess the hypothesis. The analysis result showed that all hypotheses are supported. Lastly, the result of this research will benefit the marketers for their information to understand the consumer purchase behaviour through social media during the COVID-19 pandemic.